On Style. (February 2017) - Heuer, Gottfried M.; Tudor, Keith
Abstract: This article is the result of a process and a dialogue between the two authors regarding matters of style, especially with regard to peer‐reviewed publications in this and other journals which aspire to achieving and maintaining certain academic and publishing standards. The article comprises an initial submission from the first author; email correspondence between the authors which includes some feedback from an anonymous reviewer; a short piece on style by the first author; and a final dialogue between the two authors. The article encompasses discussions about the politics of style; the implications of the expectations and, indeed, requirements of both academia and publishing; and the position of journals such as Psychotherapy and Politics International in holding and promoting a position of diversity and pluralism in the face of neoliberal pressure to conform – or be dammed.